Sams Teach Yourself Adobe® Dreamweaver® CS5 in 24 Hours - Bruce, Betsy; Ray, John 1971-; Ness, Robyn (2011)
In just 24 lessons of one hour or less, this book will show Dreamweaver beginners and upgraders how to create world-class web pages and sites with Adobe Dreamweaver. In this book's straightforward, step-by-step approach, each lesson builds on the previous ones -- helping you master all the essentials of Adobe's newest version of Dreamweaver from the ground up. Friendly, accessible, and conversational, this book gives Dreamweaver beginners a practical grounding in the entire package, without ever becoming overwhelming or intimidating. A new interactive Online Learning Lab will help you supplement the lessons in the book with step-by-step video walkthroughs of all the book's examples, detailed answers to the end-of-chapter quizzes, and all the files needed to complete the book's hands-on exercises.
Includes summary, Q&A, workshop, quiz, quiz answers, and exercises at chapter ends, and index
Keywords: Dreamweaver (Computer file); Web sites -- Authoring programs; Web sites -- Design; Sites Web; Systèmes-auteur; Sites Web; Conception; Web sites; Authoring programs; Web sites; Design; Electrical & Computer Engineering; Engineering & Applied Sciences; Telecommunications; Electronic resource; Instructional and educational works; Matériel d'éducation et de formation